Bubble concept for sporting tournaments during the COVID-19 pandemic: Football Club World Cup - Massey, A.; Lindsay, S.; Seow, D.; Gordon, J.; Lowe, D. J. (BMJ Open Sport & Exercise Medicine, 2021)
Objectives To report the person-to-staff transmission of COVID-19 with the implementation of a bubble concept that included testing, hygiene, distancing and monitoring strategies to mitigate risks.